Pengaruh Kompetensi Sumber Daya Manusia, Pemanfaatan Teknologi Informasi dan Kualitas Laporan Keuangan terhadap Kualitas Laporan Keuangan - Kusumawardhani, Fajar; Muanas, Muanas (Jurnal Ilmiah Akuntansi Kesatuan, 2020)
The purpose of this study is to find out the effects of human resources competence, the use of information technology, and the quality of accounting information system on the quality of financial statements. The research was done at PT Cipta Multi Kreasi, jl. Raya Pasar Minggu Km. 16, Jakarta. The research is a quantitative research with descriptive methods and verification was done using survey technique. The source of data is primary data. Data collection was performed through questionnaires distributed to the company’s employees. The results of the research indicate that human resources competence and the quality of information system have a significant effect to the quality of financial statement. However, the use of accounting information system does not have a significant effect on the quality of financial statements. Human resources competence, the use of information system and the quality of accounting information system simultaneously have an influence on the quality of financial statements presented by the company. Keywords:Humanresources,InformationTechnology,AccountingInformationSystems,FinancialStatements